Decoloniality praxis : the logic and ontology - Kazeroony, Hamid H. (Emerald points., 2023)
Untangling the tentacles of colonialism is not an easy task, theoretically or in practice. Presenting a holistic view of Decoloniality, its genetic makeup, and its complexities, this book examines how colonialism has become embedded in power, language, culture, institutions, and social structures across the globe, as well as what it might take to relinquish postcolonial thinking in search of a decolonized future. Incorporating perspectives from both the Global North and the Global South, this book dismantles colonial ways of thinking, clearing the way for indigenous and marginalized groups to share their knowledge and expertise in fighting global issues such as climate change. Encouraging intersectional frameworks to open up to to new possibilities for inclusion, author Hamid H. Kazeroony also explores colonization as a gendered process tied to global capitalism and what this might mean for feminist activism and scholarship. To achieve a decolonized future, we must first understand our colonial past, keeping those lessons close as we seek to reconsider and restructure the ontology of epistemic inquiries.